2020
DOI: 10.11648/j.ijovs.20200504.11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Myopia and Associated Risk Factors Among Primary Students in the Period of Online Study During COVID-19: A Cross-Sectional Study in Guangzhou

Abstract: Introduction: To investigates the impact of online study during COVID-19 on myopia in Chinese primary school students and to further analyze the influencing factors of myopia, so as to provide theoretical basis for prevention and control of myopia. Objectives: Cross-sectional study. A total of 905 primary school students from grade 1-6 in Guangzhou city were included in the study. Data were collected from uncorrected visual acuity (UCVA), non-cycloplegic photo refraction and an online questionnaire. Myopia was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This is one of the longest durations worldwide. 3,9,[12][13][14][15][16] Moreover, we had one of the longest periods of distance learning in the world (22 months). To the best of our knowledge, our study is the first to highlight important factors, such as insufficient time spent outdoors, increased recreational screen time, and younger age, that contributed to myopia progression during the pandemic based on changes in cycloplegic refraction over a three-year period in a sample with a large age range from 6 to 14 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of the longest durations worldwide. 3,9,[12][13][14][15][16] Moreover, we had one of the longest periods of distance learning in the world (22 months). To the best of our knowledge, our study is the first to highlight important factors, such as insufficient time spent outdoors, increased recreational screen time, and younger age, that contributed to myopia progression during the pandemic based on changes in cycloplegic refraction over a three-year period in a sample with a large age range from 6 to 14 years.…”
Section: Discussionmentioning
confidence: 99%
“…8 Particularly, online learning increases the prevalence of myopia at higher-grade levels due to the extended use of electronic devices. 9 Previous studies have not looked into the progression using cycloplegic refraction, which is crucial in children. 2,3 Our study aimed to investigate the effect of prolonged screen time on myopia progression in school-aged children during the pandemic of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The younger the onset of myopia, the faster the progression of myopia. 6 Education the prevalence of myopia in adolescents increases with grade level. 7 Research by (Hung et al, 2020) revealed that the increased prevalence of myopia was due to high learning activities.…”
Section: Discussionmentioning
confidence: 99%